Going through it Alone: A Cross-sectional Study on the Prevalence of Loneliness among Medical, Nursing, and Paramedical Students in a Health Science Academy in Bangalore, India - Navya P. Mangali; Bobby Joseph; Merlyn Joseph; Vilas M. Tellis (Indian Journal of Community Medicine)
Background: Life of students enrolled in a medical academy is stressful and often demanding in various aspects. Frequently, such students tend to be lonely. The prevalence of this problem has not been assessed and has been given little attention in medical schools. The objectives of this study were to determine the prevalence of loneliness among medical, nursing, and paramedical undergraduate students in a Health Science Academy in Bangalore and to assess the factors associated with loneliness among the study population. Materials and Methods: This was a cross-sectional study conducted among 400 students of a Health Science Academy and the selection of the subjects was performed by stratified random sampling. Each student was given a self-administered questionnaire which comprised of two sections. Section 1 which included the sociodemographic details and Section 2 was the revised UCLA (University of California, Los Angeles) scale (Version 3). Results: Prevalence of loneliness among the students in the academy was found to be 52%. Factors associated with loneliness and possibly contributing to it were assessed using the Mann-Whitney U test and the Pearson Chi-square test. The factors that impacted loneliness significantly were language familiarity, academics, relationships with friends, and family, health problems, and involvement in physical activities. Conclusion: The prevalence of loneliness among the students was found to be 52%. There were various factors, but despite such worrisome scores, the health science academy still ranks high in surveys that assess personality development as part of college rankings in the country. Further research would be needed to know the exact direction of association between loneliness and the associated factors.